2017
DOI: 10.29256/01.03.2017.escbm07
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Polymorphism in Patients With Juvenile Rheumatoid Arthritis

Abstract: VITAMIN D RECEPTOR GENE POLYMORPHISM IN PATIENTS WITH JUVENILE RHEUMATOID ARTHRITIS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…At the same time, it was shown that SNP ApaI ( T > G ) is associated with 25(OH)D levels in both men and women and that 25(OH)D levels were significantly lower in carriers of the TT genotype than in carriers of the GG genotype ( 60 ). The presence of the AA genotype of a polymorphic variant of BsmI is associated with a 1.84-fold increase in the risk of developing idiopathic arthritis (IA), with the presence of the A allele in the genotype being associated with a 1.34-fold increase in the probability of developing IA among patients without osteoarticular pathology ( 61 ). Kostik et al ( 62 ) reported that the BB BsmI genotype of the polymorphic marker of the VDR gene is associated with high disease activity, which can be considered as a marker of an unfavorable prognosis in boys with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it was shown that SNP ApaI ( T > G ) is associated with 25(OH)D levels in both men and women and that 25(OH)D levels were significantly lower in carriers of the TT genotype than in carriers of the GG genotype ( 60 ). The presence of the AA genotype of a polymorphic variant of BsmI is associated with a 1.84-fold increase in the risk of developing idiopathic arthritis (IA), with the presence of the A allele in the genotype being associated with a 1.34-fold increase in the probability of developing IA among patients without osteoarticular pathology ( 61 ). Kostik et al ( 62 ) reported that the BB BsmI genotype of the polymorphic marker of the VDR gene is associated with high disease activity, which can be considered as a marker of an unfavorable prognosis in boys with JIA.…”
Section: Discussionmentioning
confidence: 99%